A MAFG-lncRNA axis links systemic nutrient abundance to hepatic glucose metabolism - Marta Pradas-Juni (Nature Portfolio, 2020)
Despite widespread transcription of LncRNA in mammalian systems, their contribution to metabolic homeostasis at the cellular and tissue level remains elusive. Here Pradas-Juni et al. describe a transcription factor–LncRNA pathway that couples hepatocyte nutrient sensing to regulation of glucose metabolism in mice.